2021
DOI: 10.1038/s41467-021-23371-x
|View full text |Cite
|
Sign up to set email alerts
|

Construction 7-membered ring via Ni–Al bimetal-enabled C–H cyclization for synthesis of tricyclic imidazoles

Abstract: The construction of 7-membered ring via direct C7–H cyclization of benzoimidazoles with alkenes would provide a more atom- and step-economical route to tricyclic imidazoles and derivatives that widely exist in a broad range of bioactive molecules. However, transition metal-catalyzed C–H cyclization for medium-ring synthesis has been limited to reactive C–H bonds, instead, the activation of unreactive C–H bonds towards medium synthesis still remains an elusive challenge. Herein, we report a direct construction … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…In 2021, we reported a non-ligated Ni–Al bimetal-catalyzed C7–H cyclization of benzoimidazoles with unactivated alkenes, achieving a series of tricyclic imidazoles in up to 40–98% yield and with up to 95 : 5 ee with chiral NHCs as ligands. 44 This example revealed that the presence of Al-Lewis acid greatly enhanced the reactivity of unreactive C–H of the phenyl ring of benzoimidazoles. To enhance the reactivity of Ni–Al bimetallic catalysis, most recently, we used a phosphine oxide PO 11 -ligated Ni–Al bimetallic catalyst to explore C–H alkenylation of benzoimidazoles with alkynes, successfully realized selective C4–H alkenylation with alkynes via a rare 7-membered nickelacycle (Scheme 27).…”
Section: Phosphine Oxide-ligated Ni–al Bimetallic Catalysismentioning
confidence: 95%
“…In 2021, we reported a non-ligated Ni–Al bimetal-catalyzed C7–H cyclization of benzoimidazoles with unactivated alkenes, achieving a series of tricyclic imidazoles in up to 40–98% yield and with up to 95 : 5 ee with chiral NHCs as ligands. 44 This example revealed that the presence of Al-Lewis acid greatly enhanced the reactivity of unreactive C–H of the phenyl ring of benzoimidazoles. To enhance the reactivity of Ni–Al bimetallic catalysis, most recently, we used a phosphine oxide PO 11 -ligated Ni–Al bimetallic catalyst to explore C–H alkenylation of benzoimidazoles with alkynes, successfully realized selective C4–H alkenylation with alkynes via a rare 7-membered nickelacycle (Scheme 27).…”
Section: Phosphine Oxide-ligated Ni–al Bimetallic Catalysismentioning
confidence: 95%
“…Recently, in 2021, Ye and co-workers introduced a novel method to construct a 7-membered ring through Ni-Al bimetal-synergistic-catalyzed C7–H cyclization of alkene tethered benzoimidazoles 110a (Scheme 110). 185 This reaction gave access to a series of tricyclic imidazole compounds 110b with exclusive endo selectivity in good to excellent yields up to 98%. The Lewis acid coordination with the N-atom of imidazoles tends to decrease the electron density of the aromatic ring to promote C–H bond activation.…”
Section: Alkylation Via C–h Bond Activationmentioning
confidence: 96%
“…Ye group established a synthetic method of construction of 7-membered ring through the C 7 –H cyclization of benzoimidazoles with alkenes, which provided a more atom- and step-economical route to tricyclic imidazoles (Scheme 49). 72 Benzoimidazole-tethered alkene 91 in the presence of 10 mol% Ni(cod) 2 , 10 mol% IPrHCl, 40 mol% AlMe 3 , and 40 mol% t BuOK in toluene solvent at 130 °C for 3 h under N 2 atmosphere afforded tricyclic imidazole 92 in 40–98% yields. Electron-donating groups such as methyl and tert -butyl as well as electron-withdrawing groups such as CF 3 O, F, CF 3 , and carboxylate were found to be compatible with the reaction, yielding the desired products in 80–98% yield.…”
Section: Intramolecular Hydroarylation Reactionsmentioning
confidence: 99%